PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, DAN PELATIHAN TERHADAP KINERJA KARYAWAN DI KCU PT. BANK CENTRAL ASIA BANDA ACEH - Jessica Dhinata; Husnaina Mailisa Safitri (Universitas Muhammadiyah Aceh, 2018)
The purpose of this research are to examine the influence of leadership, organizational culture and training on employee performance at KCU PT. Bank Central Asia Banda Aceh both simultaneously and partially. The research method by describing clearly on the research objects. The research data gathered through questionnaire list and interview. The hypothesis test uses double linear regression analysis on trust level 95% (α = 0,05). The result of this research feasibility test model by using f-test (simultaneously) shows that leadership, organizational culture and training significantly influence on employee performance at KCU PT Bank Central Asia Banda Aceh. And using t-test (partial ), it shows that leadership and training significantly influence on employee performance at KCU PT. Bank Central Asia Banda Aceh, while organizational culture does not influence on employee performance at KCU PT. Bank Central Asia Banda Aceh.